Peer-support needs and experiences of young adults with chronic conditions: A mixed methods study - Katherine Melton, PhD, RN; Brynn Telenko; Peyton Miles; Sneha Dave; Sydney Reed; Rosa Kelekian, MSW; Caroline Walsh; Shannon O’Donnell; Kathleen E. Walsh, MD, MS (Health Care Transitions)
Introduction: Little is known about how young adults with chronic conditions view peer support and virtual peer-support programming. The purpose of this study is to (1) describe the psychosocial and peer support needs of young adults with different chronic conditions and (2) evaluate the acceptability of a virtual community led peer-support program. Methods: We developed and pilot-tested a 64-item online survey that included items about demographics, diagnosis and disease severity, peer support use and beliefs, program use and satisfaction, the UCLA 3-item loneliness scale, and free text responses. 136 young adults (18−35) with chronic conditions recruited from an email listserv participated. Two researchers coded free text responses and integrated quantitative and qualitative data using a convergent parallel mixed methods approach. Results: Participants expressed social isolation, difficulty connecting with healthy peers, and a desire for greater availability of peer support programs. Of the participants, 72 % (n = 96) reported a UCLA loneliness score ≥ 6, indicating loneliness. The majority (91 %, n = 119) expressed that it was important to them to know other chronically ill young adults. Only 11 % (n = 15) reported that their hospital provided peer support programming. Most (94 %;(n = 32) peer support participants were somewhat or completely satisfied with the program. Conclusions: Across different chronic conditions, peer support was seen as an unmet need and greater availability of virtual peer support programs may help support the psychosocial wellbeing of young adults with chronic conditions.